Parkinson's Disease, Speech and Neurosurgery - Thomas Ollivier; Serge Pinto; Anne‐Sophie Rolland; Emeline Cailliau; Gustavo Touzet; S. Thobois; A. Eusebio; E. Hainque; T. Rouaud; S. Drapier; D. Guehl; D. Maltete; et al. (Brain and Behavior)
ABSTRACT Background Speech impairment is a recognized but unpredictable adverse effect of sub‐thalamic nucleus deep brain stimulation (STN‐DBS) for Parkinson's disease (PD). Objectives To evaluate the prevalence of speech impairment 1 year after STN‐DBS in PD patients and to determine the predictive factors for speech outcome following STN‐DBS. Methods Data for 417 patients from the French national PREDISTIM study were collected preoperatively. The combined effect of medical treatment and surgery on speech was compared using specific items from dedicated clinical scales (MDS‐UPDRS III.1: primary endpoint) and patient self‐assessment questionnaires (items 34 and 35 of the PDQ39: secondary endpoints). For each variable, three patient groups were generated according to speech outcome at 1 year: worsening, stability, and improvement. In the second step analysis, the three groups were compared for demographic and clinical variables at baseline and STN‐DBS parameters. Results There was a significant deterioration in speech of all considered items 1 year after combined STN‐DBS and dopaminergic treatment. Four predictive factors for speech deterioration were detected: (i) the absence of preoperative speech impairment (p < 0.001); (ii) severity of motor activity of daily living (MDS‐UPDRS II off total score) (p = 0.037); (iii) high‐intensity stimulation of the left electrode (i.e., above 3.6 V) (p = 0.046); and (iv) the absence of any change in non‐motor experiences of daily life (MDS‐UPDRS I total score) (p = 0.048). Conclusions Speech outcome should be carefully monitored after STN‐DBS, especially in PD patients without preoperative speech impairment, with motor difficulties in daily‐living activities, and with increased left electrode intensity. Trial Registration ClinicalTrials.gov identifier: NCT02360683.